Registro oportunístico de Nystalus Chacuru (Piciformes: Bucconidae) predando Ameivula ocellifera (Squamata: Sauria: Teiidae) - Getulio de Assis Gurgel; Sergei Studart Quintas Filho (Heringeriana, 2014)
ABSTRACT - This note presents an opportunistic registration of predation by Nystalus chacuru on Ameivula  ocellifera, which confirms this species of lizard as an item of the diet of this bird. The observation was made  in an area of Cerrado in Federal District, Brazil.